2021
DOI: 10.1001/jamacardio.2020.5392
|View full text |Cite
|
Sign up to set email alerts
|

Association of Circulating Monocyte Chemoattractant Protein–1 Levels With Cardiovascular Mortality

Abstract: Human genetics and studies in experimental models support a key role of monocyte-chemoattractant protein-1 (MCP-1) in atherosclerosis. Yet, the associations of circulating MCP-1 levels with risk of coronary heart disease and cardiovascular death in the general population remain largely unexplored. OBJECTIVE To explore whether circulating levels of MCP-1 are associated with risk of incident coronary heart disease, myocardial infarction, and cardiovascular mortality in the general population.DATA SOURCES AND SEL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 17 publications
4
45
0
1
Order By: Relevance
“…32 Although meta-analysis revealed that higher circulating MCP-1 levels were associated with higher long- term cardiovascular mortality and increased long-term risk of stroke, its association with CAD risk was still inconsistent and few were conducted in Chinese. 11,13 The use of MR, which is less affected by issues of confounding, reverse causation and measurement error bias, is particularly useful in this context, as genetic variations closely related to the circulating level of MCP1 can be used as instrumental variables to assess their causal role in the development of CAD. 10 Previously, Georgakis et al 7 found circulating levels of MCP-1 were associated with higher risk of stroke, in particular with large-artery stroke and cardioembolic stroke.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…32 Although meta-analysis revealed that higher circulating MCP-1 levels were associated with higher long- term cardiovascular mortality and increased long-term risk of stroke, its association with CAD risk was still inconsistent and few were conducted in Chinese. 11,13 The use of MR, which is less affected by issues of confounding, reverse causation and measurement error bias, is particularly useful in this context, as genetic variations closely related to the circulating level of MCP1 can be used as instrumental variables to assess their causal role in the development of CAD. 10 Previously, Georgakis et al 7 found circulating levels of MCP-1 were associated with higher risk of stroke, in particular with large-artery stroke and cardioembolic stroke.…”
Section: Discussionmentioning
confidence: 99%
“… 32 Although meta-analysis revealed that higher circulating MCP-1 levels were associated with higher long-term cardiovascular mortality and increased long-term risk of stroke, its association with CAD risk was still inconsistent and few were conducted in Chinese. 11 , 13 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammation is a central process in the development and destabilisation of atherosclerotic plaques, leading to serious cardiovascular events such as myocardial infarction and Nutrients 2021, 13, 3047. https://doi.org/10.3390/nu13093047 https://www.mdpi.com/journal/nutrients Nutrients 2021, 13, 3047 2 of 16 stroke [1][2][3]. A number of chemokines is involved in the complex process of atherosclerotic plaque formation to recruit of various leukocytes, such as monocytes, macrophages and T lymphocytes, to the site of developing atheroma [4].…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13] The circulating level of MCP1 has been linked to cardiovascular mortality, stroke, cancers, and atrial fibrillation. [14][15][16][17][18] Genetic polymorphisms of the MCP1 gene have also been explored for their associations with various inflammation related diseases and phenotypes, including chronic periodontitis in end-stage renal disease, obstructive sleep apnea syndrome, diabetic retinopathy in type 2 diabetes mellitus, rheumatoid arthritis, tuberculosis, lupus nephritis, coronary artery disease, and COPD. [19][20][21][22][23][24][25][26] The most studies of SNPs included SNP rs1024611 (−2518 A>G), rs2857656 (−362 G>C), and rs4586 (Cys35Cys).…”
Section: Introductionmentioning
confidence: 99%